The Effect of Profitability and Leverage on Tax Planning with Company Size as a Moderating Variable - Farhana, Siti Aulia; Rumiasih, N.A; Rizqi, Muhammad Nur (Jurnal Mahasiswa Akuntansi dan Bisnis (JMAB), 2022)
The contribution of tax revenue to the Indonesian State Budget is greater than that of other sectors. The company views taxes as a burden that can reduce profits, so the company does tax planning. The tax planning strategy commonly used by companies is tax avoidance by taking advantage of the current legal loopholes. This study aims to examine the effect of profitability and leverage as well as the effect of firm size as a moderating variable on tax planning in coal mining sub-sector companies listed on the Indonesia Stock Exchange during 2016-2021. The research method used in this study is quantitative using secondary data in the form of financial statements of coal mining companies listed on the Indonesia Stock Exchange during 2016-2021. The sample of this research is 10 mining companies in the coal sub-sector with an observation period of 6 consecutive years. The data analysis technique in this study used multiple linear regression analysis and moderated regression analysis. The test results show that profitability has a significant negative effect on tax planning, leverage has a significant positive effect on tax planning, and firm size cannot moderate the effect of profitability and leverage on tax planning.